2021
DOI: 10.1002/slct.202101386
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Enhancement of Curcumin Fluorescence in PDDA and Silica Nanoparticles Coated DMPC Liposomes Based Nanocapsules: Application for Selective Estimation of ATP**

Abstract: Here we illustrate the synthesis of, 2-dimyristoyl-sn-glycero-3phosphocholine (DMPC) liposome based poly (dimethyldiallylammonium chloride) (PDDA) nanocapsule where PDDA and silica nanoparticles are coated on the surface of curcumin embedded liposomes. The prepared nanocapsule was analyzed using UV-vis spectroscopy, fluorescence spectroscopy, Dynamic Light Scattering technique, Scanning Electron Microscopy, Zeta-potential, Thermogravimetric analysis and Xray diffraction method. The fluorescence intensity of DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The limit of detection of ATP was 0.5 μM. 112 Recently, in another study, Patra et al synthesized three different nanocapsules as follows: liposomal Cur coated with a layer of PDDA, liposomal Cur coated with PDDA–silica–PDDA layer and the last nanocapsule consists of liposomal Cur–PDDA–silica–Cur–PDDA layer. They found that the fluorescence intensity of Cur in these nanocapsules considerably increased by 25, 54 and 62-fold, respectively.…”
Section: Synthesis Of Cur Loaded-msnsmentioning
confidence: 99%
“…The limit of detection of ATP was 0.5 μM. 112 Recently, in another study, Patra et al synthesized three different nanocapsules as follows: liposomal Cur coated with a layer of PDDA, liposomal Cur coated with PDDA–silica–PDDA layer and the last nanocapsule consists of liposomal Cur–PDDA–silica–Cur–PDDA layer. They found that the fluorescence intensity of Cur in these nanocapsules considerably increased by 25, 54 and 62-fold, respectively.…”
Section: Synthesis Of Cur Loaded-msnsmentioning
confidence: 99%
“…For example, liposomal curcumin nanocapsules in the presence of PDDA polymer were used to detect ATP molecule. 8 In addition, a study conducted by Bechnak et al has proven the efficiency of curcumin/F-108 polymeric nanocapsules in the detection of nucleic acid. 9 However, curcumin suffers from one major problem which is its poor bioavailability.…”
Section: Introductionmentioning
confidence: 99%